A kind of pressure-sensitive adhesive for PET protective film and preparation method thereof

By preparing an acrylic pressure-sensitive adhesive for PET protective film, the PET protective film electrostatic accumulation and electrostatic accumulation of PET protective film is solved by using modified carbon nanotubes and β-carboxyethylacrylate raw materials, and the pressure-sensitive adhesive with a mesh structure is formed. The problem of short life of antistatic agents has achieved high peel strength, good antistatic properties and stable flame retardancy.

CN118834634BActive Publication Date: 2025-02-14GUANGDONG CROWN NEW MATERIALS TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411156705.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-22
Publication Date
2025-02-14
Estimated Expiration
2044-08-22

AI Technical Summary

Technical Problem

The existing PET protective film is prone to accumulation of static electricity, resulting in problems such as vacuuming, electric shock, spontaneous combustion and even explosions. The common antistatic agents have short lifespans and poor compatibility, making them difficult to use for a long time.

Method used

A pressure-sensitive acrylic adhesive used for PET protective film is adopted, and the preparation method includes raw materials such as butyl acrylate, ethyl acrylate, acrylic acid, modified carbon nanotubes, initiators, solvents and β-carboxyethyl acrylate. Mixing, through mechanical stirring, heating, stirring and cooling, etc., forms a pressure-sensitive adhesive with a mesh structure.

Benefits of technology

The produced pressure-sensitive adhesive has high peel strength, good anti-static properties, stable and efficient flame retardant and a certain degree of heat resistance, which significantly improves the safety and service life of the PET protective film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005005179500000031
    Figure BDA0005005179500000031
  • Figure BDA0005005179500000032
    Figure BDA0005005179500000032
  • Figure BDA0005005179500000041
    Figure BDA0005005179500000041
Patent Text Reader

Abstract

The invention discloses a pressure-sensitive adhesive for a PET protective film and a preparation method thereof, and belongs to the technical field of pressure-sensitive adhesives. The invention comprises the following raw materials in parts by weight: 15-25 parts of butyl acrylate, 18-26 parts of ethyl acrylate, 4-8 parts of acrylic acid, 5-15 parts of modified carbon nanotubes, 0.1-0.3 parts of initiator, 20-30 parts of solvent, and 0.05-0.1 parts of β-carboxyethyl acrylate. The obtained pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive, which has good flexibility and is cross-linked into a mesh structure to improve the peel strength of the pressure-sensitive adhesive; wherein the modified carbon nanotubes have a reduced agglomeration phenomenon, and are grafted with organic molecular chains, which enhances the peel strength, antistatic property, flame retardancy and heat resistance of the pressure-sensitive adhesive, and the performance is long-term and stable. Therefore, the pressure-sensitive adhesive obtained by the invention has high peel strength, good antistatic property, stable and efficient flame retardancy and a certain degree of heat resistance, and has important application value in the technical field of pressure-sensitive adhesives.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of pressure-sensitive adhesives, and in particular relates to a pressure-sensitive adhesive for a PET protective film and a preparation method thereof. Background Art

[0002] PET protective film has excellent insulation, toughness, heat resistance, cold resistance, good chemical resistance and oil resistance. Due to its excellent performance, it is widely used in electronic products, optical equipment, auto parts, building materials and other fields. However, PET protective film is an insulator with large surface resistance. During production and use, static electricity is easily accumulated, resulting in dust absorption, electric shock (discharge), spontaneous combustion and even explosion, which brings inconvenience to industrial production and daily life and even endangers the personal safety of workers.

[0003] PET protective film is mainly made of PET film and pressure-sensitive adhesive through coating, drying, aging and other processes. Among them, the quality of pressure-sensitive adhesive plays a decisive role in the quality of PET protective film. Common types of pressure-sensitive adhesives include acrylic, silicone and rubber. Among them, acrylic pressure-sensitive adhesives have the characteristics of good bonding performance, low cost, stable performance and good cohesive strength. They can be applied to most application environments in production and life, and by adding antistatic agents, acrylic pressure-sensitive adhesives can also be given antistatic properties, which reduces the static electricity generated by the PET protective film when it is attached or torn off, and has great application prospects in the field of electronic and electrical products. However, common antistatic agents on the market belong to small molecules, and have poor compatibility with acrylic matrix, are easy to ooze out, have a short lifespan, and are difficult to use for a long time. In addition, acrylic ester materials have easily combustible hydrocarbon segments in structure, which are easy to burn and difficult to extinguish when exposed to fire. A large amount of smoke and toxic gases are produced when burning, which brings difficulties to fire extinguishing and also endangers human health and environmental safety. Therefore, it is urgent to invent a flame retardant and antistatic pressure sensitive adhesive for PET protective film to meet the higher demands in the field of pressure sensitive adhesive technology. Summary of the invention

[0004] The purpose of the present invention is to overcome the defects of the prior art and provide a pressure-sensitive adhesive for PET protective film and a preparation method thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a pressure-sensitive adhesive for a PET protective film comprises the following steps:

[0007] Butyl acrylate, ethyl acrylate, acrylic acid and modified carbon nanotubes are mixed, mechanically stirred for 1-2 hours, then an initiator and a solvent are added, the temperature is raised to 70-80°C, β-carboxyethyl acrylate (cross-linking agent) is added after stirring for 0.5-1.5 hours, the reaction is continued with stirring for 2-3 hours, and the mixture is cooled to room temperature to obtain a pressure-sensitive adhesive for a PET protective film.

[0008] Furthermore, the raw materials are calculated in parts by weight as follows: 15-25 parts of butyl acrylate, 18-26 parts of ethyl acrylate, 4-8 parts of acrylic acid, 5-15 parts of modified carbon nanotubes, 0.1-0.3 parts of initiator, 20-30 parts of solvent, and 0.05-0.1 parts of β-carboxyethyl acrylate.

[0009] Furthermore, the initiator is one of dibenzoyl peroxide and azobisisobutyronitrile.

[0010] Furthermore, the solvent is one of ethyl acetate, toluene and acetone.

[0011] The prepared pressure-sensitive adhesive is an acrylic pressure-sensitive adhesive. The monomer is a soft monomer, so the prepared pressure-sensitive adhesive has better flexibility. In addition, β-carboxyethyl acrylate is used as an internal cross-linking agent to promote the cross-linking of linear acrylic molecules into a network structure, thereby reducing the mobility of the molecular chains and improving the cohesive strength and peel strength of the pressure-sensitive adhesive.

[0012] Furthermore, the modified carbon nanotubes are prepared by the following steps:

[0013] S1. At room temperature and under nitrogen protection, phosphorus oxychloride, pentaerythritol and anhydrous acetonitrile were mixed uniformly in a three-necked flask equipped with a stirring reflux device, the reaction temperature was controlled to 60°C, the reaction was stirred for 5 hours, and then the temperature was raised to 115°C, and the reflux reaction was carried out until no hydrogen chloride gas was generated. After the reaction was completed, the mixture was cooled to room temperature, the solvent was removed by distillation under reduced pressure, and the mixture was washed with dichloromethane 2-3 times and dried in vacuo to obtain intermediate 1; the ratio of phosphorus oxychloride, pentaerythritol and anhydrous acetonitrile was 32.7g:13.6g:100mL;

[0014] Phosphorus oxychloride and pentaerythritol react, and the molar ratio of the two is controlled to be close to 2:1, and the phosphorus oxychloride is excessive to obtain intermediate 1; the specific reaction process is as follows:

[0015]

[0016] S2. In a three-necked flask equipped with a stirring device, the intermediate 1, hydroxyethyl acrylate, triethylamine and toluene were mixed and stirred uniformly, heated to 75° C., and kept warm for 6 hours. After the reaction was completed, the triethylamine hydrochloride was filtered out, and part of the solvent was removed by rotary evaporation. Then, the mixture was purified by column chromatography (the eluent was a mixed solvent of chloroform / ether in a volume ratio of 4:1), the eluent was removed by rotary evaporation, and vacuum dried to obtain the intermediate 2; the ratio of the amount of the intermediate 1, hydroxyethyl acrylate, triethylamine and toluene was 30.8 g:11.6 g:15 mL:120 mL;

[0017] Triethylamine is used as an acid-binding agent to remove the hydrogen chloride generated by the reaction, accelerating the reaction. Intermediate 1 undergoes a nucleophilic substitution reaction with hydroxyethyl acrylate. By controlling the molar ratio of the two to be close to 1:1 and the intermediate 1 to be slightly excessive, only one -Cl on the intermediate 1 participates in the reaction to obtain intermediate 2. The specific reaction process is shown below:

[0018]

[0019] S3. At room temperature, under nitrogen protection, 1,3-bis(aminopropyl)tetramethyldisiloxane, intermediate 2, N,N-dimethylformamide (DMF) and potassium carbonate were mixed and stirred evenly in a three-necked flask equipped with a stirring device, the reaction temperature was controlled to 70°C, the reaction was carried out for 4 hours, the reaction was completed, filtered, and part of the solvent was removed by distillation under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, and the volume ratio of the two was 5:1), the eluent was removed by rotary evaporation, and vacuum dried to obtain intermediate 3; the ratio of the amount of 1,3-bis(aminopropyl)tetramethyldisiloxane, intermediate 2, N,N-dimethylformamide, and potassium carbonate was 25.1 g:37.5 g:150 mL:13.8 g;

[0020] 1,3-bis(aminopropyl)tetramethyldisiloxane and intermediate 2 undergo nucleophilic substitution. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of 1,3-bis(aminopropyl)tetramethyldisiloxane, only one amino group on 1,3-bis(aminopropyl)tetramethyldisiloxane participates in the reaction. Potassium carbonate removes hydrogen chloride generated by the reaction to obtain intermediate 3. The specific reaction process is as follows:

[0021]

[0022] S4. In a three-necked flask equipped with a stirring device, the carboxylated carbon nanotubes were mixed with N,N-dimethylformamide, and the carboxylated carbon nanotubes were evenly dispersed by ultrasonication for 30 minutes, and then the intermediate 3 and dicyclohexylcarbodiimide (DCC) were added, and magnetic stirring was performed for 2 hours. The mixture was placed in a 55°C water bath and ultrasonicated for 2 hours. The water bath was then removed and magnetic stirring was performed at room temperature for 8 hours. The mixture was filtered, washed with anhydrous ethanol for 3-4 times, dried, and ground to obtain pre-modified carbon nanotubes. The ratio of the amount of carboxylated carbon nanotubes, N,N-dimethylformamide, intermediate 3, and DCC was 2g:100mL:5.5g:8.4g.

[0023] Under the action of DCC, -COOH on the surface of the carboxylated carbon nanotubes undergoes an amidation reaction with -NH2 on the intermediate 3, and organic molecules are grafted onto the surface of the carbon nanotubes to obtain pre-modified carbon nanotubes. The specific reaction process is as follows:

[0024]

[0025] Carbon nanotubes have high modulus, high strength and high conductivity. The modified carbon nanotubes are modified by grafting organic molecular chains, that is, an organic layer is formed on the surface of the modified carbon nanotubes, which improves the surface hydrophobicity of the carbon nanotubes, thereby enhancing the interface compatibility with the matrix, reducing the agglomeration of the carbon nanotubes in the acrylic matrix, so that the performance of the carbon nanotubes can be fully utilized, and the peel strength and antistatic properties of the matrix are greatly enhanced; in addition, the grafted organic molecular chains contain -Si-O-Si- segments, spirocyclic phosphates and acrylate structures, among which -Si-O-Si- segments are good flame retardants and smoke suppression components, which can not only improve the flame retardancy of the matrix, but also have certain Smoke suppression effect; Moreover, due to the high bond energy of Si-O bond, the heat resistance of the matrix can be improved to a certain extent; In addition, spirocyclic phosphate has good flame retardant effect and has a stable six-membered heterocyclic structure. When burning, the pentaerythritol skeleton will form a coke protective layer to inhibit further combustion of the matrix, and connect with the N element to form a PN flame retardant component, which has the synergistic flame retardant effect of phosphorus and nitrogen flame retardants, and significantly improves the flame retardant properties of the matrix; Finally, the acrylate at one end of the organic molecular chain can produce chemical bonding with the matrix in the polymerization reaction, further improving the compatibility of the modified carbon nanotubes with the matrix, and improving the stability of the modified carbon nanotubes;

[0026] It should be added that carbon nanotubes grafted with organic molecular chains can effectively prevent the migration and seepage of organic molecules, ensuring the long-term stability of various performance properties.

[0027] Furthermore, the carboxylated carbon nanotubes are prepared by the following steps:

[0028] The carbon nanotubes are placed in a conical flask, and then mixed acid is added, and ultrasonic treatment is performed in a water bath at 50°C for 4 hours. After the mixture is cooled to room temperature, deionized water is added for dilution, centrifugation is performed, and the mixture is washed with anhydrous ethanol and deionized water for 2-3 times in sequence, dried, and ground to obtain carboxylated carbon nanotubes; the mixed acid is a mixture of 98% by mass concentrated sulfuric acid and 38.8% by mass concentrated hydrochloric acid in a volume ratio of 5:1; the ratio of the carbon nanotubes to the mixed acid is 1g:100mL;

[0029] By subjecting carbon nanotubes to ultrasonic shearing and oxidation treatment with strong acid, a certain number of carboxyl active groups can be introduced into the side walls and tops of the carbon nanotubes, thus laying the foundation for reaction sites for subsequent chemical reactions.

[0030] Beneficial effects of the present invention:

[0031] 1. The pressure-sensitive adhesive prepared by the present invention is an acrylic pressure-sensitive adhesive with good flexibility, and the acrylic molecules are cross-linked into a network structure, which improves the cohesive strength and peel strength of the pressure-sensitive adhesive;

[0032] 2. By modifying the carbon nanotubes, compared with ordinary carbon nanotubes, they have better compatibility with the matrix, significantly reduce the agglomeration phenomenon, and greatly enhance the peel strength and antistatic properties of the pressure-sensitive adhesive;

[0033] 3. The various groups in the organic molecular chains on the modified carbon nanotubes work synergistically, significantly improving the flame retardancy and heat resistance of the pressure-sensitive adhesive to a certain extent; and the performance is long-term and stable, without the need for additional additives, ensuring the homogeneity of the pressure-sensitive adhesive;

[0034] Therefore, the pressure-sensitive adhesive prepared by the present invention has high peeling strength, good antistatic performance, stable and efficient flame retardancy and a certain degree of heat resistance, and has important application value in the field of pressure-sensitive adhesive technology. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] Preparation of carboxylated carbon nanotubes:

[0038] 10 g of carbon nanotubes were placed in a conical flask, and then 1000 mL of concentrated sulfuric acid (mass fraction 98%) and concentrated hydrochloric acid (mass fraction 38.8%) were added in a volume ratio of 5:1 to obtain a mixed acid, and the mixture was ultrasonically treated in a 50°C water bath for 4 h. After the mixture was cooled to room temperature, deionized water was added to dilute it, centrifuged, and washed with anhydrous ethanol and deionized water for 3 times in sequence, dried, and ground to obtain carboxylated carbon nanotubes.

[0039] Example 2

[0040] Preparation of modified carbon nanotubes:

[0041] S1. At room temperature and under nitrogen protection, 32.7 g of phosphorus oxychloride, 13.6 g of pentaerythritol and 100 mL of anhydrous acetonitrile were mixed evenly in a three-necked flask equipped with a stirring reflux device, the reaction temperature was controlled to 60°C, the reaction was stirred for 5 hours, and then the temperature was raised to 115°C, and the reaction was refluxed until no hydrogen chloride gas was generated. After the reaction was completed, the mixture was cooled to room temperature, the solvent was distilled off under reduced pressure, the mixture was washed with dichloromethane 2-3 times, and vacuum dried to obtain intermediate 1;

[0042] S2, in a three-necked flask equipped with a stirring device, 30.8g of intermediate 1, 11.6g of hydroxyethyl acrylate, 15mL of triethylamine and 120mL of toluene were mixed and stirred uniformly, heated to 75°C, and kept warm for 6h. After the reaction was completed, triethylamine hydrochloride was filtered out, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of chloroform / ether, and the volume ratio of the two was 4:1), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain intermediate 2;

[0043] S3, at room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring device, 25.1g 1,3-bis(aminopropyl)tetramethyldisiloxane, 37.5g intermediate 2, 150mL N,N-dimethylformamide (DMF) and 13.8g potassium carbonate were mixed and stirred uniformly, the reaction temperature was controlled to 70°C, the reaction was carried out for 4h, the reaction was completed, filtered, and part of the solvent was distilled off under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, the volume ratio of the two was 5:1), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain intermediate 3;

[0044] S4. In a three-necked flask equipped with a stirring device, mix 2 g of the carboxylated carbon nanotubes prepared in Example 1 with 100 mL of N,N-dimethylformamide, and ultrasonicate for 30 min to evenly disperse the carboxylated carbon nanotubes. Then add 5.5 g of intermediate 3 and 8.4 g of dicyclohexylcarbodiimide, and stir magnetically for 2 h. Put it in a 55°C water bath and ultrasonicate for 2 h. Then remove the water bath and stir magnetically for 8 h at room temperature. Filter, wash with anhydrous ethanol 3-4 times, dry, and grind to obtain pre-modified carbon nanotubes.

[0045] Example 3

[0046] Preparation of modified carbon nanotubes:

[0047] S1. At room temperature and under nitrogen protection, 65.4 g of phosphorus oxychloride, 27.2 g of pentaerythritol and 200 mL of anhydrous acetonitrile were mixed evenly in a three-necked flask equipped with a stirring reflux device, the reaction temperature was controlled to 60°C, the reaction was stirred for 5 hours, and then the temperature was raised to 115°C, and the reaction was refluxed until no hydrogen chloride gas was generated. After the reaction was completed, the mixture was cooled to room temperature, the solvent was distilled off under reduced pressure, the mixture was washed twice with dichloromethane, and vacuum dried to obtain intermediate 1;

[0048] S2, in a three-necked flask equipped with a stirring device, 61.6g of intermediate 1, 23.2g of hydroxyethyl acrylate, 30mL of triethylamine and 240mL of toluene were mixed and stirred uniformly, heated to 75°C, and kept warm for 6h. After the reaction was completed, triethylamine hydrochloride was filtered out, and part of the solvent was removed by rotary evaporation. Then, it was purified by column chromatography (the eluent was a mixed solvent of chloroform / ether, and the volume ratio of the two was 4:1), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain intermediate 2;

[0049] S3, at room temperature, under nitrogen protection, in a three-necked flask equipped with a stirring device, 50.2g of 1,3-bis(aminopropyl)tetramethyldisiloxane, 75g of intermediate 2, 300mL of N,N-dimethylformamide and 27.6g of potassium carbonate were mixed and stirred uniformly, the reaction temperature was controlled to 70°C, the reaction was carried out for 4h, the reaction was completed, filtered, and part of the solvent was distilled off under reduced pressure, and then purified by column chromatography (the eluent was a mixed solvent of petroleum ether / ethyl acetate, the volume ratio of the two was 5:1), the eluent was removed by rotary evaporation, and vacuum drying was performed to obtain intermediate 3;

[0050] S4. In a three-necked flask equipped with a stirring device, 4 g of the carboxylated carbon nanotubes prepared in Example 1 were mixed with 200 mL of N,N-dimethylformamide, and ultrasonicated for 30 min to evenly disperse the carboxylated carbon nanotubes. Then, 11.0 g of intermediate 3 and 16.8 g of dicyclohexylcarbodiimide were added, and magnetic stirring was performed for 2 h. The mixture was placed in a 55°C water bath and ultrasonicated for 2 h. The water bath was removed and magnetic stirring was performed for 8 h at room temperature. The mixture was filtered, washed with anhydrous ethanol for 3 times, dried, and ground to obtain pre-modified carbon nanotubes.

[0051] Example 4

[0052] 15 g of butyl acrylate, 18 g of ethyl acrylate, 4 g of acrylic acid and 5 g of the modified carbon nanotubes prepared in Example 2 were mixed, mechanically stirred for 1 h, 0.1 g of dibenzoyl peroxide and 20 g of toluene were added, the temperature was raised to 70°C, stirred for 0.5 h, 0.05 g of β-carboxyethyl acrylate was added, the reaction was continued with stirring for 2 h, and the mixture was cooled to room temperature to obtain a pressure-sensitive adhesive for PET protective film.

[0053] Example 5

[0054] 20 g of butyl acrylate, 22 g of ethyl acrylate, 6 g of acrylic acid and 10 g of the modified carbon nanotubes prepared in Example 3 were mixed, mechanically stirred for 1 hour, 0.2 g of azobisisobutyronitrile and 25 g of ethyl acetate were added, the temperature was raised to 75°C, 0.1 g of β-carboxyethyl acrylate was added after stirring for 1 hour, the reaction was continued with stirring for 3 hours, and the mixture was cooled to room temperature to obtain a pressure-sensitive adhesive for PET protective film.

[0055] Example 6

[0056] 25 g of butyl acrylate, 26 g of ethyl acrylate, 8 g of acrylic acid and 15 g of the modified carbon nanotubes prepared in Example 3 were mixed, mechanically stirred for 2 h, 0.3 g of azobisisobutyronitrile and 30 g of acetone were added, the temperature was raised to 80° C., 0.1 g of β-carboxyethyl acrylate was added after stirring for 1.5 h, the reaction was continued with stirring for 3 h, and the mixture was cooled to room temperature to obtain a pressure-sensitive adhesive for PET protective film.

[0057] Comparative Example 1

[0058] Ordinary carbon nanotubes of the same mass were used to replace the modified carbon nanotubes in Example 6, and the remaining steps were the same as in Example 6 to prepare a pressure-sensitive adhesive.

[0059] Comparative Example 2

[0060] A commercially available phosphorus-based flame retardant of equal mass was used to replace the modified carbon nanotubes in Example 6, and the remaining steps were the same as in Example 6 to prepare a pressure-sensitive adhesive.

[0061] Comparative Example 3

[0062] Use commercially available high temperature resistant acrylic pressure sensitive adhesive.

[0063] Examples 4-6 and Comparative Examples 1-3 were coated on a stainless steel plate, and after drying, the flame retardant properties of the samples were measured before and after being placed at room temperature for 180 days using the national standard GB / T2408-2008 "Determination of Combustion Performance of Plastics - Horizontal and Vertical Methods";

[0064] Examples 4-6 and Comparative Examples 1-3 were coated on a stainless steel plate, and after drying, the peel strength was measured using the national standard GB / T2792 "180° peel strength test method for pressure-sensitive adhesive tapes";

[0065] Examples 4-6 and Comparative Examples 1-3 were coated on a stainless steel plate, and after drying, placed in an oven at 120° C. for 8 h, taken out and naturally cooled to room temperature, and the residual adhesive was observed after peeling;

[0066] The examples 4-6 and comparative examples 1-3 were uniformly coated on a PET substrate, kept at 100°C for 1.5 min, and then aged at 48°C for 25 h to obtain a PET protective film. The thickness of the PET substrate was 40 μm, and the thickness of the pressure-sensitive adhesive layer was 10 μm. The protective film was cut into a size of 10*10 mm, the release film was torn off, and the adhesive surface resistance was tested on a high resistance meter.

[0067] The measured results are shown in the following table:

[0068]

[0069] It can be seen from the above table that the pressure-sensitive adhesive prepared in the embodiment of the present invention has high peel strength, good antistatic performance, stable and efficient flame retardancy and a certain degree of heat resistance, and has important application value in the field of pressure-sensitive adhesive technology.

[0070] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0071] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for preparing a pressure-sensitive adhesive for a PET protective film, characterized in that: The following steps are involved: Butyl acrylate, ethyl acrylate, acrylic acid and modified carbon nanotubes are mixed, mechanically stirred, an initiator and a solvent are added, the temperature is increased and stirred, β-carboxyethyl acrylate is added, the reaction is continued by stirring, and the mixture is cooled to room temperature to obtain a pressure-sensitive adhesive for a PET protective film; The modified carbon nanotubes are prepared by the following steps: S1. At room temperature and under nitrogen protection, phosphorus oxychloride, pentaerythritol and anhydrous acetonitrile were mixed evenly, reacted at 60°C for 5 hours, then heated to 115°C, refluxed until no hydrogen chloride gas was generated, the reaction was completed, cooled to room temperature, distilled under reduced pressure, washed, and dried in vacuo to obtain intermediate 1; S2, mixing intermediate 1, hydroxyethyl acrylate, triethylamine and toluene, stirring evenly, reacting at 75° C. for 6 h, filtering, rotary evaporating, column chromatography purification, rotary evaporating, and drying to obtain intermediate 2; S3, at room temperature, under nitrogen protection, 1,3-bis(aminopropyl)tetramethyldisiloxane, intermediate 2, N,N-dimethylformamide and potassium carbonate were mixed and stirred evenly, reacted at 70°C for 4 hours, and after the reaction was completed, filtered, distilled under reduced pressure, purified by column chromatography, rotary evaporated, and dried to obtain intermediate 3; S4, mixing the carboxylated carbon nanotubes with N,N-dimethylformamide, ultrasonicating for 30 min, then adding the intermediate 3 and dicyclohexylcarbodiimide, magnetically stirring for 2 h, ultrasonicating at 55° C. for 2 h, then removing the water bath magnetic stirring for 8 h, filtering, washing, drying, and grinding to obtain pre-modified carbon nanotubes; The carboxylated carbon nanotubes are prepared by the following steps: The carbon nanotubes were placed in a conical flask, and then mixed acid was added, and ultrasonic treatment was performed in a 50°C water bath for 4 hours. After the mixture was cooled to room temperature, deionized water was added for dilution, centrifuged, and washed with anhydrous ethanol and deionized water for 2-3 times in sequence, dried, and ground to obtain carboxylated carbon nanotubes; the mixed acid was a mixture of 98% by mass concentrated sulfuric acid and 38.8% by mass concentrated hydrochloric acid in a volume ratio of 5:1; the ratio of carbon nanotubes to mixed acid was 1g:100mL.

2. The method for preparing a pressure-sensitive adhesive for a PET protective film according to claim 1, characterized in that: The raw materials are calculated in parts by weight as follows: 15-25 parts of butyl acrylate, 18-26 parts of ethyl acrylate, 4-8 parts of acrylic acid, 5-15 parts of modified carbon nanotubes, 0.1-0.3 parts of initiator, 20-30 parts of solvent, and 0.05-0.1 parts of β-carboxyethyl acrylate.

3. The method for preparing a pressure-sensitive adhesive for a PET protective film according to claim 1, characterized in that: The initiator is one of dibenzoyl peroxide and azobisisobutyronitrile.

4. The method for preparing a pressure-sensitive adhesive for a PET protective film according to claim 1, characterized in that: In step S1, the ratio of phosphorus oxychloride, pentaerythritol and anhydrous acetonitrile is 32.7 g:13.6 g:100 mL.

5. The method for preparing a pressure-sensitive adhesive for a PET protective film according to claim 1, characterized in that: In step S2, the ratio of the amount of intermediate 1, hydroxyethyl acrylate, triethylamine and toluene is 30.8 g:11.6 g:15 mL:120 mL.

6. The method for preparing a pressure-sensitive adhesive for a PET protective film according to claim 1, characterized in that: In step S3, the ratio of the amount of 1,3-bis(aminopropyl)tetramethyldisiloxane, intermediate 2, N,N-dimethylformamide, and potassium carbonate is 25.1 g:37.5 g:150 mL:13.8 g.

7. The method for preparing a pressure-sensitive adhesive for a PET protective film according to claim 1, characterized in that: In step S4, the ratio of the amount of carboxylated carbon nanotubes, N,N-dimethylformamide, intermediate 3, and dicyclohexylcarbodiimide is 2 g:100 mL:5.5 g:8.4 g.

8. A pressure-sensitive adhesive for PET protective film, characterized in that: Prepared according to the method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • High-temperature-resistant acrylic pressure-sensitive adhesive and preparation method thereof as well as pressure-sensitive adhesive tape and preparation method thereof

    CN114921202A

  • High-temperature-resistant high-conductivity pressure-sensitive adhesive and preparation method thereof

    CN115418182A